Komunitas Makrozoobentos di Sungai Gua Pintu Ngalau pada Kawasan Karst di Sumatera Barat - Husnul Mar’i; Izmiarti Izmiarti; Nofrita Nofrita (Jurnal Biologi Universitas Andalas, 2017)
Pintu Ngalau cave is flowed by river from irrigated rice fields that flows into the cave. This cave has a source of organic matter derived from bats and swallow dirts, litter that falls on enterance of the cave and the organic material carried by the flow of the river. The study on the macrozoobenthos communities of river in Pintu Ngalau Cave has been conducted from October until November 2016. The study used survey method, where stratified random sampling was applied in three zones (light zone, dim zone and dark zone) at study site. Macrozoobenthos samples was collected by surber net. This study also measured the physic-chemical of water. The results showed the composition of macrozoobenthos in the Pintu Ngalau cave river consisted of 43 genera i.e Gastropods (2 genera), Hirudinea (2 genera), Insects (36 genera) and Oligochaetas (3 genera). Total density of macrozoobenthos in this site was 2100 ind/m2 and the highest density was found in dark zone. The highest total relative density (KR total=79,89%) on genus level at every zone was Hydropsyche. Diversity index of macrozoobenthos was classified as medium (H'=2.68) with evenness distribution was evenly (E=0.61) and no dominant genus (C=0.14). The existence of macrozoobenthos was not influenced by light intensity, but instead was more influence by the condition of the substrate and the flow of water in the cave.